(untitled) (Research, Society and Development, 2026)
Background: Cholecystectomy is a common procedure in children with Sickle Cell Disease (SCD) due to the high prevalence of gallstones. However, the perioperative period poses a high risk for the development of Acute Chest Syndrome (ACS), a severe and potentially fatal pulmonary complication in this population. Objective: To estimate the pooled incidence of ACS in the postoperative period following cholecystectomy in children and adolescents with SCD. Methods: A systematic review with single proportion meta-analysis was conducted following PRISMA guidelines. Searches were performed in PubMed/MEDLINE, ScienceDirect, LILACS, and Google Scholar, with no date or language restrictions. Observational studies reporting the occurrence of post-cholecystectomy ACS in SCD patients aged ≤18 years were included. Risk of bias was assessed using the ROBINS-I tool. Synthesis was performed using a random-effects model with Freeman-Tukey transformation. Results: Seven studies (638 procedures) were included. The pooled incidence of ACS was 4.32% (95% CI: 2.41% – 5.99%), with moderate to substantial heterogeneity (I² = 57.65%). Individual rates ranged from 0% to 20%. Sensitivity analysis confirmed the robustness of the result. Publication bias was not detected. The overall quality of evidence was limited by moderate to serious risk of bias in the primary studies. Conclusion: Approximately 1 in 23 children with SCD undergoing cholecystectomy develops postoperative ACS. This non-negligible risk reinforces the need for detailed preoperative counseling, active postoperative monitoring, and the implementation of standardized, multidisciplinary perioperative protocols to mitigate this serious outcome.